Promoter activity and transcript mapping in the regulatory region for genes encoding ribosomal protein S15 and polynucleotide phosphorylase of Escherichia coli - Evans, Sylvia (Gene, 1985)
The genes encoding ribosomal protein S15 (rpsO) and polynucleotide phosphorylase (pnp) occupy adjacent positions and are oriented in the same direction on the Escherichia coli chromosomes. The nucleotide sequence of the region controlling the expression of these two genes has been determined. Two in-phase gene fusions between pnp and lacZ were constructed. The fusions define the translational reading frame of the pnp gene and indicate that the expression of pnp is independent of the upstream rpsO gene. Transcript mapping with nuclease S1 demonstrated that the two genes are transcribed from separate promoters and that the rpsO-pnp intergenic space contains a strong transcriptional terminator. The transcriptional start points have been localized.